TINJAUAN HUKUM ISLAM TERHADAP PERSELINGKUHAN AKIBAT TIDAK TERPENUHINYA NAFKAH MATERI DARI SUAMI - wahyuddin; mursalin (P3M STAI DDI Mangkoso, 2024)
This research aims to examine the problem of infidelity due to the wife's failure to provide material support in the light of Islamic law. This research also starts from a true story of a wife who in recent years complained about her husband's treatment of not having the means to provide material support for his wife or children, even though the husband was born capable of working to earn a living, so the wife was fed up with her husband's treatment. this is by cheating. Therefore, the main focus of this research is to understand the concept, essence, rights, and obligations of husband and wife as well as their implications for infidelity according to the legal perspective in force in Indonesia, be it public law (criminal), private law (civil) or Islamic law which contains sharia. – Islamic law. The research method used is a qualitative approach, which involves conducting interviews with individuals and informants considered capable in their fields to explain this problem. It is hoped that the research results can contribute to society in increasing understanding of legal aspects, livelihood obligations, and the implications of infidelity from the perspective of Islamic law and sharia.